2019
DOI: 10.2478/popets-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

Cardinality Estimators do not Preserve Privacy

Abstract: Cardinality estimators like HyperLogLog are sketching algorithms that estimate the number of distinct elements in a large multiset. Their use in privacysensitive contexts raises the question of whether they leak private information. In particular, can they provide any privacy guarantees while preserving their strong aggregation properties?We formulate an abstract notion of cardinality estimators, that captures this aggregation requirement: one can merge sketches without losing precision. We propose an attacker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 39 publications
2
51
0
Order By: Relevance
“…As an aside, our privacy risk analysis differs considerably from Desfontaines, et al (2018), who argue that "cardinality estimators do not preserve privacy." However, their threat model includes an adversary who has incremental access to the sketches as they are being generated, rather than only a single sketch per hospital for a query.…”
Section: B Privacy Risk Score --Anonymitymentioning
confidence: 97%
“…As an aside, our privacy risk analysis differs considerably from Desfontaines, et al (2018), who argue that "cardinality estimators do not preserve privacy." However, their threat model includes an adversary who has incremental access to the sketches as they are being generated, rather than only a single sketch per hospital for a query.…”
Section: B Privacy Risk Score --Anonymitymentioning
confidence: 97%
“…To the authors' best knowledge, there is no previous work on the security of HLL. The closest works focus on the privacy implications of HLL [11] or on attacks on data structures like Bloom filters or the Count-Min sketch [12].…”
Section: Arxiv:200206463v1 [Cscr] 15 Feb 2020mentioning
confidence: 99%
“…This would make harder for the attacker to identify which elements modify the cardinality estimation. However, it seems that the attacker could still get that information [11]. This can be done by testing different combinations of elements repeatedly.…”
Section: Existing Techniquesmentioning
confidence: 99%
“…Recently, Desfontaines et al [18] considered privacy of cardinality estimators from a different angle. In particular, they assumed an insider risk scenario where the adversary has access to the actual sketch (rather than the output statistic) and showed that no noiseless sketch can be differentially private.…”
Section: Secure Statisticsmentioning
confidence: 99%
“…Recently, a seemingly contradictory result has been published. In particular, Desfontaines et al [18] showed that the LogLog sketch does not protect privacy from the inside attacker who has access to the sketch. Their result is not in conflict with our result in this section, since they assumed that the inside attacker also knows the hash key whereas our result assumes the private hash function.…”
Section: A Single-party Protocolmentioning
confidence: 99%